2014
DOI: 10.3758/s13421-014-0435-9
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the effect of self-directed study on episodic memory

Abstract: Self-directed learning is often associated with better long-term memory retention, however, the mechanisms that underlie this advantage remain poorly understood. This series of experiments was designed to “deconstruct” the notion of self-directed learning in order to better identify the factors most responsible for these improvements to memory. In particular, we isolate the memory advantage that comes from controlling the content of study episodes from the advantage that comes from controlling the timing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 35 publications
6
58
0
Order By: Relevance
“…The present paper compares the effects of active and yoked study on 5-to 10-year-old children's learning. Experiment 1 replicates the design from previous adult studies (Markant et al, 2014;. Experiment 2 replicates and extends the results from Experiment 1 to further explore the effects of differential pre-exposure on children's studying strategies.…”
Section: Benefits Of Active Learning On Memorymentioning
confidence: 59%
See 1 more Smart Citation
“…The present paper compares the effects of active and yoked study on 5-to 10-year-old children's learning. Experiment 1 replicates the design from previous adult studies (Markant et al, 2014;. Experiment 2 replicates and extends the results from Experiment 1 to further explore the effects of differential pre-exposure on children's studying strategies.…”
Section: Benefits Of Active Learning On Memorymentioning
confidence: 59%
“…An important role for experimental psychology is to assess if and how these bedrock educational principles align with what we know about the basic mechanisms of learning and memory. Indeed, a number of recent experiments with adults have shown that minimal forms of volitional control (specifically, allowing learners to select the order and pacing of study) lead to memory improvements compared to study situations lacking this control (Harman, Humphrey, & Goodale, 1999;Voss, Warren, et al, 2011;Voss, Galvan, & Gonsalves, 2011;Voss, Gonsalves, Federmeier, Tranel, & Cohen, 2011;Liu, Ward, & Markall, 2007;Meijer & Van der Lubbe, 2011;Markant, DuBrow, Davachi, & Gureckis, 2014;Plancher, Barra, Orriols, & Piolino, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Agency, or the ability to exert control by causally influencing choice outcomes, has been shown to facilitate memory in adults (Gureckis & Markant, 2012;Voss, Galvan, & Gonsalves, 2011;Voss, Gonsalves, Federmeier, Tranel, & Cohen, 2011) and in children (Ruggeri, Markant, Gureckis, Bretzke, & Xu, 2019). Even relatively inconsequential control, like determining the timing of the onset of stimuli (Markant, DuBrow, Davachi, & Gureckis, 2014) or merely having the opportunity to make a choice (Murty, DuBrow, & Davachi, 2015) enhances subsequent memory for the resulting outcomes. Although a large corpus of work has demonstrated that agency facilitates memory across development, it is still unclear why individuals are more likely to remember the consequences of their own actions.…”
Section: Introductionmentioning
confidence: 99%
“…There is one finding in the literature that suggests that control over onsets may be valuable in controlling learning. Markant, DuBrow, Davachi, and Gureckis (2014) demonstrated that control over the shifting of windows within a spatial self-exploration task (Voss, Gonsalves, Federmeier, Tranel, & Cohen, 2011) enhanced learning relative to a passive control. Perceived control over learning environments has been linked to enhanced memory through interaction between the striate and the hippocampus (Murty, DuBrow, & Davachi, 2015).…”
Section: Effectiveness Of Self-directed Learningmentioning
confidence: 99%